2006
DOI: 10.1128/jb.01953-05
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Immunity and Host Chromosome Integration Site of P2-Like Coliphages

Abstract: The amount and distribution of variation in the genomic region containing the genes in the lytic-lysogenic genetic switch and the sequence that determines the integration site into the host chromosome were analyzed for 38 P2-like phages from Escherichia coli. The genetic switch consists of two convergent mutually exclusive promoters, Pe and Pc, and two repressors, C and Cox. The immunity repressor C blocks the early Pe promoter, leading to the establishment of lysogeny. The Cox repressor blocks expression of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Results showed that when the main target site was inaccessible, either due to the presence of another prophage or because of an induced mutation, prophages integrated within a secondary site located in the host chromosome. This finding is consistent with other published reports (4,16).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Results showed that when the main target site was inaccessible, either due to the presence of another prophage or because of an induced mutation, prophages integrated within a secondary site located in the host chromosome. This finding is consistent with other published reports (4,16).…”
Section: Discussionsupporting
confidence: 83%
“…This can also explain the variability observed in the STEC strains. Another plausible explanation is that in double lysogens, homologous recombination between the two phages can serve as the causative agent for the selection of two different sites (16). However, since in our experiments conducted with the mutant strain there was only one phage, homologous recombination between two prophages was not possible.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations